A new species of Limnofregata (Pelecaniformes: Fregatidae) from the Early Eocene Wasatch Formation of Wyoming: implications for palaeoecology and palaeobiology. (24th October 2014) - Stidham, Thomas A.; Angielczyk, Kenneth
Abstract A humerus and a coracoid from the Early Eocene Wasatch Formation in the Washakie Basin of south‐western Wyoming are the oldest materials (by ~2 million years) of the pelecaniform Limnofregata (Aves) and represent a new large species, Limnofregata hutchisoni sp. nov. This fossil is the oldest known member of the frigatebird lineage. Other than its large size relative to Limnofregata azygosternon and L. hasegawai, the new material is very similar morphologically to other known Limnofregata specimens. The size of this new species is comparable to the largest living species (e.g. Fregata minor and Fregata magnifiscens) and much larger than the two described species of Limnofregata. This fossil indicates that the hard minimum date previously advocated for molecular calibration of the split between Fregatidae and Suloidea is an underestimate by approximately two million years. The presence of early pelecaniform bird lineages (represented by Limnofregata and Masillastega) in limnic ecosystems prior to their known occurrences in marine deposits/habitats appears to indicate that some clades of pelecaniform birds may have undergone an evolutionary transition from freshwater to marine habitats in a pattern reminiscent of what has been suggested during the evolution of pinnipeds or that their palaeoecology included broader niches ranging across a variety of aquatic habitats. That transition in habitat occupation and the origin of many of the characteristic biological aspects present in the crown frigatebird clade likely occurred during a significant temporal gap (> 45 million years) in the fossil record of the frigatebird lineage after these earliest occurrences in the Early Eocene and before the oldest records of the extant Fregata species in the Pleistocene.